Unveiling nexus between live streaming, trust, and fashion products purchase decision in Indonesian e-commerce - Ria Sulastri; Bintoro Bagus Purmono; Erna Listiana; Titik Rosnani; Muhammad Irfani Hendri (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This research aims to investigate the impact of live streaming on purchase decisions and the mediating role of trust.Method — This research adopts a quantitative approach and utilizes Structural Equation Modeling (SEM) along with AMOS 24 statistical software for data analysis. The data were gathered through a questionnaire, employing a purposive sampling technique with 210 respondents.Result — The results of this research indicate that both live streaming and trust exert a positive and significant impact on purchase decisions. Additionally, live streaming demonstrates a positive and significant influence on trust. Trust is identified as a mediator between live streaming and purchase decisions.Novelty — This research centers on examining the role of live streaming in shaping purchase decisions for fashion products in Indonesian e-commerce. Unlike previous studies that primarily explore the impact of live streaming on social media, this research expands its scope by conducting a comprehensive analysis of its overall influence on purchasing decisions.